PRACTICAL USAGE OF CROSS-CULTURAL TEXTS IN THE CLASSES OF UKRAINIAN AS A FOREIGN LANGUAGE - Denysiuk, Nadia; Nazarevych, Lesia; Babiak, Zhanna (Mountain School of Ukrainian Carpaty, 2021)
The article is devoted to a topical issue: the study of cross-cultural texts as the main communicative tool in Ukrainian language classes as a foreign language. The ideas presented in the article are illustrated by examples based on the experience of teaching Ukrainian as a foreign language at Ternopil Ivan Puluj National Technical University (TNTU). The analysis of modern researches and publications is carried out. The importance of considering the linguistic and cultural approach is emphasized, as well as the emotional component, choosing songs, phrases, colloquialisms, and thematic texts. Based on the lyrical song "Hutsulka Ksenia", the authors demonstrated how at the level of themes, images, and tokens it is possible to tell foreign communicators about mental features of Hutsuls, culture, nature, and folk instruments. A number of methodical developments on e-platforms are given: open4ukrainian.education/gutsulka-ksenya/;http://bit.ly/rizdvyanipisni-kolyadki, the benefits of working with online tools are revealed: Wizer.me (https://wizer.me/), Learningapps (https://learningapps.org), which are very important in distance learning languages. The objective of the article is to draw attention of teachers-practitioners to the need of selecting educational materials with consideration of the expediency and practical application of information; to focus on the development of communicative competence; to prove the relevance of a variety of tasks and examples; to share the experience of teaching the Ukrainian language among foreign students. The hermeneutic, communicative, cultural and other methods are applied in the research; the importance of visualization of pre-text and posttext exercises, questions, post-text comments is studied. The methodological basis of this research is the work of Anna Shvets “Theory and practice of teaching the Ukrainian language to foreign students of humanities: a monograph” (Shvets, 2019). The content of cross-cultural texts, which contribute to the formation of linguistic and local lore knowledge about Ukraine, and help foreign students adapt to Ukraine and be acquainted with its realities, is analyzed and described.